Factors Affecting the Academic Performance of Elementary Teacher Education Students in DOrSU-San Isidro Campus, Philippines - Bugwak, Elven Ruelo (Jurnal Pendidikan Progresif, 2023)
Factors Affecting the Academic Performance of Teacher Education Students in DOrSU-San Isidro Campus. Objective: This quantitative research study aimed to determine the factors affecting the academic performance of students from DOrSU-San Isidro Campus. Methods: This study made use of a quantitative type of research design specifically descriptive-survey research design. Mean and standard deviation were used in this study. Findings: It is found out that the set of factor that has the highest mean has moderate impact on elementary teacher education students’ academic performance. Conversely, the set of factors that have low impact on elementary teacher education students’ academic performance are personal condition, study habits, home-related factors and lecturer factor. Conclusions: It can be concluded that factors such as personal condition, study habits, home-related factors, and lecturer factor have low impact on the academic performance of elementary teacher education students. On the other hand, school-related factors have a moderate impact on the academic performance of elementary teacher education students. With that, schools and their administrators should look into providing students with conducive learning environment. Keywords: teacher education, academic performance, survey research design, Philippines.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202316